Survival rate and mortality risk factors among TB–HIV co-infected patients at an HIV-specialist hospital in Myanmar: A 12-year retrospective follow-up study. (March 2019) - Aung, Zaw Zaw; Saw, Yu Mon; Saw, Thu Nandar; Oo, Nwe; Aye, Hnin Nwe Ni; Aung, Sithu; Oo, Htun Nyunt; Cho, Su Myat; Khaing, Moe; Kariya, Tetsuyoshi; Yamamoto, Eiko; Hamajima, Nobuyuki
Highlights: Two out of five TB–HIV patients died within 10 years after antiretroviral therapy initiation. About one third of patients reported unknown HIV transmission routes. The 5- and 10-year survival rates were 82.0% and 58.1%, respectively. Abstract: Background: Myanmar is listed as one of the countries with the highest burden of tuberculosis and HIV infections (TB–HIV) in the world. However, the survival rate and risk factors for mortality among TB–HIV co-infected patients in the country remain unstudied. Therefore, the purpose of this study was to examine these factors. Methods: A 12-year retrospective follow-up study was conducted among 3598 TB–HIV co-infected patients (2452 male and 1146 female) aged 15 years and above, enrolled on antiretroviral therapy (ART) from July 1, 2005 to December 31, 2016. Hazard ratios (HR) were estimated using the Cox proportional hazards model. Survival rates at the beginning of ART were calculated using the Kaplan–Meier method. Results: A total of 494 (13.7%) patients died during this period. The survival rate of TB–HIV co-infected patients was 82.0% at 5 years and 58.1% at 10 years. The risk factors for mortality were being bedridden (adjusted hazard ratio (aHR) 2.70, 95% confidence interval (CI) 2.13–3.42), having a low baseline CD4 count (aHR 1.53, 95% CI 1.25–1.87), and being on a second-line ART regimen (aHR 8.12, 95% CI 3.56–18.54). Conclusions: Two out of five TB–HIV patients died within 10 years after ART initiation. Current HIV prevention and treatment programs should focus more on bedridden patients, those on second-line ART, and those with low baseline CD4 counts.